Enhancement in the field emission behavior of graphene in N-2/O-2 high vacuum ambience - Suryawanshi, S. R.; Kolhe, Pankaj S.; Gavhane, D. S.; Patil, S. S.; Chavan, P. G.; More, Mahendra A.; Late, Dattatray J. (2014 27th International Vacuum Nanoelectronics Conference (IVNC), 2014)
Herein we report, pressure dependent field emission (FE) behaviour of a few-layer graphene emitter. Gas dependent FE properties have been investigated in ultra high vacuum (UHV), as well as in N-2 and O-2 ambience at base pressure similar to 1x10(-6) torr. Interestingly, the graphene emitter when operated in N-2/O-2 ambience exhibits lower turn-on field and higher emission current density, as compared to the UHV conditions. The emission current stability investigated at preset value of similar to 1 mu A over the period of more than 2 hrs is found better in the N2 ambience and is characterized by fewer fluctuations, in contrast to the behaviour in the O-2 ambience. The observed enhanced electron emission behavior in N-2/O-2 ambience is attributed to modulation of the work function of graphene emitter.
Keywords: graphene; Pressure Dependent Field Emission

Photo-enhanced field emission studies of tapered CdS nanobelts - Chavan, Padmakar G.; More, Mahendra A.; Joag, Dilip S.; Badadhe, Satish S.; Mulla, Imtiaz S. (2014 27th International Vacuum Nanoelectronics Conference (IVNC), 2014)
Field emission and photo-enhanced field emission characteristics of single crystalline tapered CdS nanobelts have been investigated. The turn-on field for the emission current density of similar to 0.1 mu A/cm(2) is found to be similar to 2.1 V/mu m, which is much lower than reported values for various CdS nanostructures. The photo-enhanced field emission current shows a reproducible photo-switching behavior with rise in current level nearly four times that of its initial preset value (similar to 1 mu A) which is found to be very remarkable. Possible mechanism of photo-enhanced field emission is discussed.
Keywords: Current stability; field emission; Nanobelts; Photoswitching